A multidisciplinary, multifaceted improvement initiative to eliminate mislabelled laboratory specimens at a large tertiary care hospital. Issue 8 (9th June 2014) - Seferian, Edward G; Jamal, Salima; Clark, Kathleen; Cirricione, Mary; Burnes-Bolton, Linda; Amin, Mahul; Romanoff, Neil; Klapper, Ellen
Abstract : Objectives: To sustainably reduce the rate of mislabelled laboratory specimens through implementation of a series of interventions as led and coordinated by a multidisciplinary performance improvement team. Methods: The quality improvement project was performed at Cedars-Sinai Medical Center in Los Angeles, an academic care tertiary care hospital. Phlebotomy services are provided by unit-based nursing and dedicated laboratory-based phlebotomists. Baseline mislabelled specimen rate was obtained for a 6-month period prior to the first improvement intervention. Included in the rate of mislabelled specimens were inpatient blood and body fluid specimens. Anatomic pathology and cytological specimens and outpatient specimens were excluded. Mislabelled specimens were identified preanalytically, analytically or postanalytically. A specimen was considered mislabelled under the following circumstances: (1) specimen/requisition mismatch; (2) incorrect patient identifiers and (3) unlabelled specimen. Specimen mislabels were identified and validated monthly by a multidisciplinary team composed of personnel from nursing, laboratory and performance improvement. Performance improvement initiatives were implemented over a 2-year period with control charts used to assess improvement over time. Results: The rate of mislabelled specimens varied by clinical area and decreased significantly over a 24-month time period during the initiative from 4.39 per 10 000 specimens to 1.97 per 10 000 specimens. All clinical areas achieved a significant decrease in the rate of mislabelled specimens except for the operating room and labour and delivery. Conclusions: A multidisciplinary unit specific approach using performance improvement methodologies focusing on human factors can reliably and sustainably reduce the rate of mislabelled laboratory specimens in a large tertiary care hospital.